A systematic review and meta-analysis of randomized controlled trials investigated the effects of melatonin supplementation on bone mineral density, quality of life, and sleep in menopausal women - Du, Ji; Tan, Yong (Frontiers in Nutrition, 2026)
ObjectiveThis study evaluated the impact of melatonin supplementation on bone mineral density (BMD), sleep quality, menopausal symptoms, mood, sexual function, serum insulin levels, and body mass index in menopausal women.Evidence reviewA systematic literature review and meta-analysis were conducted using PubMed/MEDLINE, Embase, and Web of Science (2015–2024), following PRISMA guidelines. The risk of bias was assessed with the Cochrane tool.FindingsAnalysis of 7 groups (497 participants) indicated that melatonin may increase bone mineral density (BMD), particularly in the femoral neck, based on two randomized controlled trials (RCTs). However, high heterogeneity prevented pooled statistical analysis. No significant improvements were observed in sleep quality, menopausal symptoms, anxiety, depression, sexual function, BMI, or insulin levels. Side effects were similar across groups.ConclusionAvailable evidence suggests that melatonin-containing supplements may be associated with improved BMD in menopausal women, but the independent effect of melatonin and an optimal dose remain unclear due to heterogeneity in interventions and the prevalent use of combination therapies. For other outcomes (sleep, menopausal symptoms, mood, sexual function, BMI, and insulin), the evidence is currently inconclusive. Further large-scale RCTs are needed to confirm these findings.